Encountering aged care: a mixed methods investigation of medical students' clinical placement experiences. Issue 1 (December 2016) - Annear, Michael; Lea, Emma; Lo, Amanda; Tierney, Laura; Robinson, Andrew
Abstract Background Residential aged care is an increasingly important health setting due to population ageing and the increase in age-related conditions, such as dementia. However, medical education has limited engagement with this fast-growing sector and undergraduate training remains primarily focussed on acute presentations in hospital settings. Additionally, concerns have been raised about the adequacy of dementia-related content in undergraduate medical curricula, while research has found mixed attitudes among students towards the care of older people. This study explores how medical students engage with the learning experiences accessible in clinical placements in residential aged care facilities (RACFs), particularly exposure to multiple comorbidity, cognitive impairment, and palliative care. Methods Fifth-year medical students (N  = 61) completed five-day clinical placements at two Australian aged care facilities in 2013 and 2014. The placements were supported by an iterative yet structured program and academic teaching staff to ensure appropriate educational experiences and oversight. Mixed methods data were collected before and after the clinical placement. Quantitative data included surveys of dementia knowledge and questions about attitudes to the aged care sector and working with older adults. Qualitative data were collected from focus group discussions concerning medical student expectations, learning opportunities, and challenges to engagement. Results Pre-placement surveys identified good dementia knowledge, but poor attitudes towards aged care and older adults. Negative placement experiences were associated with a struggle to discern case complexity and a perception of an aged care placement as an opportunity cost associated with reduced hospital training time. Irrespective of negative sentiment, post-placement survey data showed significant improvements in attitudes to working with older people and dementia knowledge. Positive student experiences were explained by in-depth engagement with clinically challenging cases and opportunities to practice independent clinical decision making and contribute to resident care. Conclusions Aged care placements can improve medical student attitudes to working with older people and dementia knowledge. Clinical placements in RACFs challenge students to become more resourceful and independent in their clinical assessment and decision-making with vulnerable older adults. This suggests that aged care facilities offer considerable opportunity to enhance undergraduate medical education. However, more work is required to engender cultural change across medical curricula to embed issues around ageing, multiple comorbidity, and dementia.